Hepatitis B Awareness and Knowledge in Asian Communities in British Columbia - Alan Hoi Lun Yau; Jo-Ann Ford; Peter Wing Cheung Kwan; Jessica Chan; Queenie Choo; Tim K. Lee; Willie Kwong; Alan Huang; Eric Yoshida (Canadian Journal of Gastroenterology and Hepatology)
Background. Our study examined hepatitis B virus (HBV) awareness and knowledge in Asian communities in British Columbia (BC). Methods. A statistical random sample representation of Chinese, Korean, Filipino, South Asian, and Southeast Asian populations in Greater Vancouver was surveyed by telephone. Multiple logistic regression analysis was performed to identify predictors of HBV knowledge. Results. General awareness of HBV was reported in 78.8% (798/1013). HBV awareness was the highest in Chinese (89%) and Filipino (88%) populations and the lowest in the South Asian (56%) population. “Reasonable” knowledge of HBV was elicited in 76.8% (778/1013). Higher HBV knowledge was associated with younger age (p=0.014), higher education (p<0.0001), Chinese ethnicity (p<0.0001), and use of media (p=0.01) and Internet (p=0.024) for health information. Compared to the Chinese (OR = 1.0) population, “reasonable” knowledge of HBV was lower in Korean (OR = 0.3, 95% CI: 0.1–0.5), Filipino (OR = 0.3, 95% CI: 0.2–0.6), South Asian (OR = 0.3, 95% CI: 0.2–0.4), and Southeast Asian (OR = 0.3, 95% CI: 0.1–0.6) populations. 54.8% (555/1013) felt that HBV education was inadequate and 80.1% (811/1013) preferred HBV education in their native languages. Conclusion. Compared to the Chinese population, other Asian communities in BC have lower HBV awareness and knowledge. Public education should target older and less educated and Korean, Filipino, South Asian, and Southeast Asian populations in their native languages via media and Internet.